The effect of cleaning ultrafiltration membrane using different concentration of NaOH - Mohd Farridd, Ahmad Termizi (2006)
The developments of membrane technology are currently increased in parallel with the wide requirement. This happen because many application of this membrane technology. One of the applications from membrane technology is treatment of waste water as this experiment withheld. The study of mercury separation in deionized (DI) water using Ultrafiltration (UF) membrane to make sure whether UF membrane can separate mercury in the solution or not. This study using (UF) without the basis of PVDF. Besides, this study was held for pressure from 1.5-10.5 bar. If the optimum pressure of 5 bar, permeate flux value is as low as1.82Lm2/min and retentate flux value is as high as 18.02Lm2/min achieved. Concentration value at retentate is high showing that the presences of mercury inhibit in the sample compare to original (DI) water. Concentration value achieved at retentate is about 2.0µg/L and permeate value is 1.0µg/L. After running separation process, observed that the product flow will be constant starting at the first 20 minutes to 40 minutes. This happen because pores on the Ultrafiltration membrane surface clogged with mercury. In order to clean pores, 5 concentration parameter NaOH for 0.1M, 0.2M, 0.3M, 0.4M, 0.5M recommended for cleaning process. From overall results, 0.5M NaOH is suitable for cleaning process of (UF) membrane according to graph plotted as same as standard graph that we get from first experiment.